2015
DOI: 10.13189/ujme.2015.030302
|View full text |Cite
|
Sign up to set email alerts
|

Three Dimensional Finite Element Analysis of Wire Drawing Process

Abstract: This work aims to analytically and numerically study the parameters affecting on the wire drawing process using a 3D finite element model and the effect of these parameters on drawing force. Three-dimensional finite element model using DEFORM-3D V6.1 was built to simulate this process. AL-1100 wire was drawn through a conical die with semi-die angle ( α = 6° , 8° , 8.5° , 9° , 9.5° , 10°,, 15° ), reduction ratio ( r = 0.1 , 0.15 , 0.2 , 0.25 , 0.3), friction coefficient ( µ = 0.1 , 0.08 , 0.075 , 0.07 , 0.065 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…On the other hand, the bearing length (0.3 d → 0.2 d) was reduced in order to protect the tantalum wire from damage. In the case of ductile metals, there is the possibility of a fault occurring in the wire during drawing due to the drawing force [32]. Therefore, we concluded that shortening the bearing length was advantageous for processing.…”
Section: Resultsmentioning
confidence: 87%
“…On the other hand, the bearing length (0.3 d → 0.2 d) was reduced in order to protect the tantalum wire from damage. In the case of ductile metals, there is the possibility of a fault occurring in the wire during drawing due to the drawing force [32]. Therefore, we concluded that shortening the bearing length was advantageous for processing.…”
Section: Resultsmentioning
confidence: 87%
“…The wire drawing is one of the most process which are widely used in metal forming [1]. It is a process of reducing the wire diameter by drawing it through a conical die [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is so that, by the use of numerical models and methods, Chen and Huang [3] and Majzoobi et al [4] determined that 2β, Hc and the temperature profile into the die have a significant effect on the drawing process, but it is very important to consider the effect of the wire-die contact length (l) which determines the contact surface at the interface and has a direct effect on the lubrication conditions and, as a consequence, on the value of the friction coefficient µ, involved in the process. Another consulted works demonstrated the feasibility of the use of FEM applied to model the wiredrawing process and focused on the improvement of the geometry of the die [13], on the analysis of the strain distribution in the wire during the process [14] or even to analyze the distribution of residual stresses accumulated in the product once it has been shaped [15], among other output variables. On the other hand, considering all the input factors previously exposed, the effect of drawing speed (v) on the tribological system must be considered since previous works demonstrated that, at high drawing speeds, a localized and intense heating effect is implied in the contact zone which can be detrimental to maintain the properties of the lubricant, worsening the tribological conditions [16,17].…”
Section: Introductionmentioning
confidence: 99%